Pengaruh Aktivitas Wanita Wirausaha Terhadap Pertumbuhan Usaha Olahan Kentang di Kabupaten Kerinci, Jambi - Silvia Sari; Wahyu Budi Priatna; Burhanuddin Burhanuddin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
Indonesia need to strengthen the national economy to face the AEC (ASEAN Economic Community) in the end of 2015 by growing Micro Small and Medium Enterprises (SMEs) which has entrepreneurial characteristics. Currently there is an increasing activity of women in SMEs. This research aimed at identifying and analyzing the forming factors of women’s entrepreneurial activities that contribute to grow new enterprise on processed potato business.This study is located in Kerinci regency because there were increased entrepreneurial activity by women. Primary data were collected through questionnaire to 111 women entrepreneurs of potato processing by the sampling “census” technique, and the data were analyzed by Structural Equation Modeling (SEM). The exogenous latent variables were entrepreneurial characteristics, personal characteristics, opportunity, and resources. Where as women’s entrepreneurial activities and grow new enterprise as endogenous latent variables. The results showed that the built model had goodness fit and good reliability measurement variables (CR≥0.70, VE≥0.50). Women entrepreneurial activities were reflected the most by resources (γ=0.66) and entrepreneurial characteristics (γ=0.59). Entrepreneurial characteristics of women entrepreneur were formed by motivation (λ= 0.54), risk taking (λ= 0.32), and innovation (λ= 0.95). Thus women who processing potatoes in Kerinci regency have the entrepreneurial character. Women’s entrepreneurial activities positively proved contribute to grow new enterprise on processed potato business (β=0.95). Facilitating new venture program, strengthening of capital program, and business training to women entrepreneurs should be a priority of the Indonesian government programs in the future to compete in the AEC (ASEAN Economic Community).